Development of skull fracture criterion based on real-world head trauma simulations using finite element head model. (April 2016) - Sahoo, Debasis; Deck, Caroline; Yoganandan, Narayan; Willinger, Rémy
Abstract: The objective of this study was to enhance an existing finite element (FE) head model with composite modeling and a new constitutive law for the skull. The response of the state-of-the-art FE head model was validated in the time domain using data from 15 temporo-parietal impact experiments, conducted with postmortem human surrogates. The new model predicted skull fractures observed in these tests. Further, 70 well-documented head trauma cases were reconstructed. The 15 experiments and 70 real-world head trauma cases were combined to derive skull fracture injury risk curves. The skull internal energy was found to be the best candidate to predict skull failure based on an in depth statistical analysis of different mechanical parameters (force, skull internal energy), head kinematic-based parameter, the head injury criterion (HIC), and skull fracture correlate (SFC). The proposed tolerance limit for 50% risk of skull fracture was associated with 453 mJ of internal energy. Statistical analyses were extended for individual impact locations (frontal, occipital and temporo-parietal) and separate injury risk curves were obtained. The 50% risk of skull fracture for each location: frontal: 481 mJ, occipital: 457 mJ, temporo-parietal: 456 mJ of skull internal energy.